E-commerce: understanding consumer perceptions towards online bus ticket reservation system / Mohd Zarif Mohd Zaki - Mohd Zaki, Mohd Zarif (2005)
Problems associated with the ticketing system remain as the long unresolved issues in the public transportation industry in Malaysia. It is a common see bus stations thronged by thousands of people during weekends or public holidays when many Malaysians rush to get seats on the many express bus services to return to their hometowns. The intercity express bus industry has indeed been entrenched as the top choice mode of public transportation in Malaysia. Nevertheless, the poor coordination of bus tickets distribution causes unnecessary congestions at main bus terminals nationwide. The growth of electronic commerce (E-Commerce) in the country has provided another means of solving the ticketing problem by the employing E-Commerce applications to introduce .an online ticket reservation system. Several local bus operators have made the service available for quite a few years, but the utilization of the service is still below par. This study aims to investigate the consumers' perceptions towards the online ticket reservation system. Various aspects of the consumers have been surveyed such as, their demographic profiles, travel history, awareness of the online ticket reservation system as well as prior experiences in the utilization of the online ticket reservation service. The results and findings of the study can be used as guidelines for bus operators as well as the other interested parties, in implementing the online bus ticket reservation system.